MESIN PEMISAH LOGAM MENGGUNAKAN CONVEYOR DAN PNEUMATIK BERBASIS PLC - S, Sarip udin; Pratama, Aditya (Jurnal TEDC; Vol 19 No 3 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i3.1326, 2025)
This research discusses the development of an automated system that integrates pneumatic technology and PLC-based control for the purpose of separation and transportation of goods. This system is designed to enhance efficiency in the production and logistics processes. By applying pneumatic principles, this machine can accurately separate various types of items based on specific criteria. The use of PLC as the central control allows precise coordination in managing pneumatic mechanism movements. Experimental results demonstrate the success of the system in performing the intended separation functions. With the implementation of this system, it is expected to optimize production and logistics processes in various industrial sectors.